The Effect of Roll Maintenance Costs on Kiln Machines on the Efficiency of Expenditure on PT. XYZ - Chaerudin, Abdul Rauf (Bina Bangsa International Journal of Business and Management, 2022)
PT. XYZ is a company engaged in the ceramics industry. One way maintenance is carried out on production machines is to use the cost of maintenance expenditure which aims to streamline and expedite the production process of both quality and quantity. In this study the cost pemeliharaanyang done is on a production machine roller kiln kiln mainly because if not maintained can quickly roll the kiln was dirty and broken so that it can directly increase the cost of expenditures (the smaller the efficiency of expenditures) for the purchase of a new kiln roll to replace the roll kiln dirty and broken. The method used in this study to determine the effect of roller kiln maintenance costs on the efficiency of spending is a statistic that is a quantitative method with simple linear regression (two variables). From the research results obtained regression equation y = 0.379 +1.110 X diliat coefficients table from SPSS, Efficiency of expenditure will be worth 0.379 if the company no roll maintenance costs. Each one-time increase in the cost of engine maintenance roll kiln then the efficiency corporate spending rose by 1.110. The cost of engine maintenance roll kilns have strong relationships with significant spending efficiency by 97.9% results from SPSS can diliat model summary table, the efficiency of spending can be influenced by other factors is the use of EUT. Average roll kiln is unplugged as much as 105.73 in round roll 106 at a price of Rp 300,000 a roll when not using the average maintenance cost per month can pay for purchases of new roll of 106 x 300 000 = 31.8 million. If using the maintenance costs (usage Grinding stone) at a price of Grinding stones, Rp. 1.800.000 to clean up the dirty roll kiln as many as 100-150 stems roll is clearly more efficient in spending comparedWith no use of maintenance costs